2021
DOI: 10.24258/jba.v17i1.721
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Kebijakan Masa Pandemi Covid-19: Sebuah Sanggahan Atas Artikel Widaningrum dan Mas'udi (2020)

Abstract: Widaningrum and Mas'udi (2020) believe that the government's stuttering in handling the COVID-19 pandemic trigger policy conflicts between government officials and at the society level. Widaningrum and Mas'udi (2020) view that strengthening leadership and coördination are important steps to prevent widespread policy conflicts. However, in using the PCF framework, Widaningrum and Mas'udi (2020) forgot to place the policy conflict on what level was the political system, policy subsystem or policy action? We use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Menyikapi krisis kesehatan/pandemi ini, kebijakan pemerintah Indonesia pada awal-awal terjadinya pandemi dinilai kurang ada sinkronisasi antaraktor pemerintahan, meskipun menurut Kamim (2021) hal ini dipandang menjadi sesuatu yang lumrah sebagai bentuk pembelajaran kebijakan antarpihak mengingat kebaruan peristiwa pandemi COVID-19. Berbicara mengenai kebijakan pemerintah terutama yang menyangkut bidang sosial ekonomi, pembahasan akan selalu menarik jika melihat seberapa jauh kebijakan tersebut lebih memihak kepada masyarakat dan bukan kepentingan politis atau bisnis semata.…”
Section: Pendahuluanunclassified
“…Menyikapi krisis kesehatan/pandemi ini, kebijakan pemerintah Indonesia pada awal-awal terjadinya pandemi dinilai kurang ada sinkronisasi antaraktor pemerintahan, meskipun menurut Kamim (2021) hal ini dipandang menjadi sesuatu yang lumrah sebagai bentuk pembelajaran kebijakan antarpihak mengingat kebaruan peristiwa pandemi COVID-19. Berbicara mengenai kebijakan pemerintah terutama yang menyangkut bidang sosial ekonomi, pembahasan akan selalu menarik jika melihat seberapa jauh kebijakan tersebut lebih memihak kepada masyarakat dan bukan kepentingan politis atau bisnis semata.…”
Section: Pendahuluanunclassified
“…Furthermore, Kamim (2021) explores the policy for handling Covid-19 in Indonesia through the Advocacy Coalition Framework (ACF) to understand how advocacy coalitions in the policy subsystem try to make policy changes by setting a belief system and policy-oriented policy learning. This study found 2 (two) main things that competed in the Covid-19 handling policy subsystem.…”
Section: Introductionmentioning
confidence: 99%